Diversidade de uso do solo no entorno das estações de metrô em São Paulo - André de Freitas Gonçalves (Confins)
Urban densification around metro stations has been used as a means to achieve the reduction of travel distance and time, promotion of active and collective transportation. We used the land use diversity indicator as a way to characterize the surroundings of metro stations in the city of São Paulo, pointing to homogeneity or heterogeneity of urban space use. In a complementary manner, we identify the predominant uses by means of clustering. The combination of both techniques evidences the amplitude of land use diversity and its relationship with the predominant clusters.